Implementasi permainan tradisional engklek untuk meningkatkan interaksi sosial anak di Madrasah Ibtidaiyah - Purwati, Dwi (Maliki Interdisciplinary Journal, 2025)
This article discusses the implementation of traditional games to improve social interaction among elementary school children. Given current technological advances, traditional games, which are usually played by children in the afternoon, continue to be replaced by gadgets that are now indispensable in various aspects of life. Gadgets make it difficult for children to interact with their peers and the people around them. Madrasah Ibtidaiyah forms the basis for developing good character that will be beneficial for children’s future. Technology is advancing rapidly, leading to dependence on gadgets and delayed child development, ranging from emotional issues to reduced physical exploration and creativity. In addition, a lack of social interaction and verbal stimulation can hinder the development of speech and language skills. Social interaction requires repeated practice to make it easier for children when they enter higher education. Traditional games are an effort to help children become interested in learning in a fun but serious way. Engklek is one game that can be used to support children’s development in school. By providing this game in between sports activities, children become interested in learning and will continue to be enthusiastic about playing it. Thus, this method is very effective for teaching children in Madrasah Ibtidaiyah and can preserve Indonesian culture so that children are also more familiar with their regional culture.